Lower COVID-19 Mortality in Patients with Type 2 Diabetes Mellitus Taking Dipeptidyl Peptidase-4 Inhibitors: Results from a Turkish Nationwide Study - ARĞA, KAZIM YALÇIN (SPRINGER HEIDELBERG, 2021)
Introduction To investigate the effect of preexisting treatment with dipeptidyl peptidase-4 inhibitors (DPP-4is) on COVID-19-related hospitalization and mortality in patients with type 2 diabetes mellitus (T2DM). Methods A multicenter, retrospective cohort study was conducted using patient data extracted from the Turkish National Electronic Database. All patients who tested positive for COVID-19 (PCR test) between 11 March through to 30 May 2020 were screened for eligibility (n = 149,671). Following exclusion of patients based on pre-determined inclusion criteria, patients with T2DM using a DPP-4i or glucose-lowering medications other than a DPP-4i were compared for mortality and hospitalization. The propensity score method was used to match age, gender, micro- and macrovascular complications, and medications in the two groups. Independent associates of mortality were analyzed using multivariable analysis on the whole T2DM population. Results A total of 33,478 patients with T2DM who tested postive for COVID-19 who met the inclusion criteria were included in the analysis. Median (interquartile range) age was 54 (22) years and 42.4% were male. Of these, 9100 patients using DPP-4is (n = 4550) or other glucose-lowering drugs (n = 4550) were matched in two groups. After matching, analysis revealed a lower mortality in the DPP-4i group (9.5 vs. 11.8%; p < 0.001). In the multivariable model, the use of DPP-4is (odds ratio [OR] 0.57, 95% confidence interval [CI] 0.35-0.91; p = 0.02) was associated with lower mortality in the whole sample, while age, male gender, computed tomography finding of COVID-19, obesity, low glomerular filtration rate, and an insulin-based regimen also predicted increased risk of death. There was no association between the preexisting treatment with DPP-4is and COVID-19-related hospitalization in the matched analysis or multivariate model. The rate of admission to the intensive care unit and/or mechanical ventilation favored the DPP-4i group (21.7 vs. 25.2%; p = 0.001), although this association became saturated in the multivariate analysis (OR 0.65, 95% CI 0.39-1.08; p = 0.099). Conclusions The results of this study demonstrate an association between DDP-4i use and reduced mortality in people with T2DM who tested PCR positive for COVID-19.
Keywords: Type 2 diabetes mellitus; COVID-19; Hospitalization; Intensive care unit admission; Mechanical ventilation; Mortality; DPP-4 inhibitor; Anti-diabetic agents; ASSOCIATION; DISEASE; SEVERITY; OUTCOMES